Synthesis, structural and sorption characterization of a Hofmann compound, Ni(3-methy-4, 4′-bipyridine)[Ni(CN)4]. (15th May 2021) - Wong-Ng, W.; Culp, J.; Siderius, D.W.; Chen, Y.; Wang, S.Y.G.; Allen, A.J.; Cockayne, E.
Graphical abstract: Highlights: Guest-filled and guest-free Ni-BpyMe were successfully synthesized and characterized. Different crystal structures due to different ligand ring orientations for preventing pore collapse. Type-I sorption curves (absence of hysteresis loops). Abstract: Acetone extraction of crystalline Ni(CN)4 -based metal organic framework Ni(3-Methy-4, 4′-bipyridine)[Ni(CN)4 ] which has dimethyl sulfoxide "DMSO" as guest molecules (nicknamed Ni-BpyMe(D) followed by evacuation yielded the guest-free crystalline framework, (Ni-BpyMe(A)). Ni-BpyMe(A) was determined to be orthorhombic, Pmma, a = 12.6025(4) Å, b = 7.3324(3) Å, c = 11.3095(4) Å, V = 1045.07 (2) Å 3 and Z = 2. The structure of Ni-BpyMe(A) consists of a 3-D net built from extended 2-D [Ni(CN)4 ] groups. These layers are connected to each other via the BpyMe ligands at the six-fold coordinated Ni1 site while Ni2 has a four-fold coordination environment. While forming infinite square nets, the [Ni(CN)4 ] chains progress in a zig-zag fashion along the ab -direction; they can be projected along a or b directions. Another feature of this structure is that instead of locating the –CH3 group in one position of the pyridine ring as expected, it appears to be in two mirror-related positions on the same pyridine ring. The structure represents an average of two configurations which gives rise to the pseudosymmetry. The methyl group is distributed equally among each side of the pyridine ring; therefore, the occupancy of the methyl group is 50%. The compound exhibits a Type-I sorption characteristic. The absence of a hysteresis loop indicates that it is not likely a flexible MOF. A comparison of the structure of Ni-BpyMe(A) with the previously reported structure of Ni-BpyMe(D) with DMSO as guest molecules revealed a different structure (Monoclinic P 2 /n ) as a result of significant increase in the bipyridyl dihedral angle from 34.87° to 90.00° after removal of the guest molecules in the pores. The change in ring orientation of the BpyMe ligands stabilize the pore structure against collapse. The structural change is relevant to gate opening behaviors observed in other MOFs although no gating behavior was indicated in the gas adsorption behavior.